How Did Veterans' Reliance on Veterans Health Administration Outpatient Care Change After Expansion of the Veterans Community Care Program?. Issue 10 (11th October 2022) - Sterling, Ryan A.; Liu, Chuan-Fen; Hebert, Paul L.; Fortney, John C.; Swankoski, Kaylyn E.; Katon, Jodie G.; Wong, Edwin S.
Abstract : Background: The Veterans Community Care Program (VCCP) aims to address access constraints in the Veterans Health Administration (VA) by reimbursing care from non-VA community providers. Little existing research explores how veterans' choice of VA versus VCCP providers has evolved as a significant VCCP expansion in 2014 as part of the Veterans Access, Choice, and Accountability Act. Objectives: We examined changes in reliance on VA for primary care (PC), mental health (MH), and specialty care (SC) among VCCP-eligible veterans. Research Design: We linked VA administrative data with VCCP claims to retrospectively examine utilization during calendar years 2016–2018. Subjects: 1.78 million veterans enrolled in VA before 2013 and VCCP-eligible in 2016 due to limited VA capacity or travel hardship. Measures: We measured reliance as the proportion of total annual outpatient (VA+VCCP) visits occurring in VA for PC, MH, and SC. Results: Of the 26.1 million total outpatient visits identified, 45.6% were for MH, 29.9% for PC, and 24.4% for SC. Over the 3 years, 83.2% of veterans used any VA services, 23.8% used any VCCP services, and 20.0% were dual VA-VCCP users. Modest but statistically significant declines in reliance were observed from 2016–2018 for PC (94.5%–92.2%), and MH (97.8%–96.9%), and a more significant decline was observed for SC (88.5%–79.8%). Conclusions: Veterans who have the option of selecting between VA or VCCP providers continued using VA for most of their outpatient care in the initial years after the 2014 VCCP expansion.